Vertical Transmission of Hepatitis B Virus is the most Important Route of Transmission in Asymptomatic Carriers in Bangladesh (TAJ: Journal of Teachers Association, 2010)
To find out the route of the transmission of HBV in asymptomatic carrier and build up awareness against the transmission of HBV. It was a prospective study in the Dept. of Medicine (IPD & OPD) and Transfusion Medicine in Rajshahi Medical College Hospital from June 2005 to July 2007. 300 asymptomatic carriers of HBV were included. HBsAg was detected incidentally during routine screening tests done for blood donation programme, foreign mission and courses abroad. All the HBsAg positive patients were confirmed by doing HBsAg (ELISA) tests after 6 months. All were positive. Among 300 asymptomatic carriers male 270 and female 30. Age between 15 to 35 yrs. HBeAg positive only in 15 patients. ALT above 60 U/L in 17 patients, HBV-DNA (PCR) detectable in 15 patients, coarse liver echotexture in 20 patients, Oesophageal Varix small size in 02 patients. Serum Albumin, PT, AFP all were normal range. Screening of all the family members of the carriers was done. Among the 300 index cases 130 (43.33%) family members most likely mother,father, brother, sister or cousin were HBVmarkers positive. Liver related death was present in 50 families (16.66%} HBV transmission is preventable. Mass education is required about the transmission of HBV. Screening of HBV should be mandatory in all pregnant women. Bangladesh Government has integrated the HBV vaccination in EPI. DOI: 10.3329/taj.v22i1.5027 TAJ 2009; 22(1): 97-100